Localization of vascular endothelial growth factor and its receptor, flt, in human placenta and decidua by immunohistochemistry - Jason Cooper; Andrew Sharkey; J. McLaren; D. Stephen Charnock‐Jones; S. K. Smith (1995)
Vascular endothelial growth factor is a secreted angiogenic growth factor the mRNA of which is present in the placenta. The mRNA encoding the vascular endothelial growth factor receptor, flt, has also been demonstrated in placenta, with trophoblast appearing to be a novel site of flt expression. We investigated the expression of both vascular endothelial growth factor and flt-like immunoreactivity in first trimester and term placentae. In the first trimester, vascular endothelial growth factor immunoreactivity was localized to placental macrophages (Hofbauer cells), and in decidua, to glandular epithelium and maternal macrophages. In the term placenta, vascular endothelial growth factor immunoreactivity was present in extravillous trophoblast and in extracellular material. Flt immunoreactivity was demonstrated on extravillous trophoblast in first trimester and term, and on Hofbauer cells within placental villi. This complex pattern of both vascular endothelial growth factor and flt-like immunoreactivity suggests that vascular endothelial growth factor may be involved not only in the regulation of placental angiogenesis, but also in trophoblast invasion.